THE EFFECT OF A TRAINING PROGRAM ON DIFFERENT SURFACES IN DEVELOPING THE FOREHAND AND BACKHAND SKILLS OF JUNIOR TENNIS PLAYERS - Mohammed Taqi, Israa Hassan (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
This study aims to evaluate the effect of a training program on different surfaces in developing the forehand and backhand skills of junior tennis players. An experimental approach with a pre-test and post-test design was used, with participants divided into two experimental groups. The players performed tests to measure the accuracy and technical performance of the skills. The training program was implemented using various surfaces, including grass and clay courts. The results showed significant improvements in performance and accuracy for both skills in the experimental groups after the training program, highlighting the importance of surface diversity in enhancing player performance.